Evaluating the outcomes of cancer patients receiving palliative care in Botswana - Radikara, Naledi (Department of Medicine, 2026)
Botswana is an upper middle-income country in Sub-Saharan Africa that is experiencing a growing incidence of cancer and other Non-Communicable Diseases and is at the early stages of implementing Palliative Care (PC). PC has been shown to enhance the quality of life (QoL) of patients and their families, consequently improving their health outcomes. This research will emphasise the importance of PC in the Botswana health care system and aims to determine the outcomes of patients under palliative care at Princess Marina Hospital (PMH). Methods: We prospectively enrolled 53 consecutive patients with a diagnosis of metastatic and/or progressive cancer who were referred to the PC team for the first time from March 2023 to November 2023. The primary end-point was a change in symptoms and QoL from baseline to four (4) weeks as per the APCA African POS questionnaire and the ECOG PS tool. Participants were assessed initially at entry to PC services and again after 4 weeks while under PC. Results: A total of 53 participants were included in the initial assessment while 42 were included in both the initial and subsequent assessments, indicating an attrition rate of 21%. The top 5 cancers were: breast (20.8%), cervical(15.1%), prostate(9.4%), anorectal(9.4%) and oesophageal(9.4%). Symptoms occurring in at least 50% of the participants were: pain (94.3%), weakness (75.5%), nausea (58.5%), loss of appetite (64.1%), constipation (50.9%), dry mouth (69.8%), drowsiness (56.6%), poor mobility (54.7%) and worry (90.6%). The results showed that the difference was statistically significant between the two -time points for pain (z=2.707, p = 0.0068), shortness of breath (z=2.261, p=0.0238), nausea (z=3.275, p=0.0011), loss of appetite (z=2.480, p=0.0131), constipation (z=2.832, p=0.0046), drowsiness( z=3.091, p=0.0020), ability to share feelings with family and friends(z=0.701, p=0.0069) and advice to plan for the future(z=2.586, p=0.0097).Vomiting(z=0.982, p=0.326), dry mouth(z=1.466, p=0.1426) , poor mobility(z=1.922, p=1.922), feelings of worry( z= 1.127, p=0.2596), feeling that life is worthwhile(z=1.330, p=0.1835) and feeling at peace(z=1.651, p=0.0987) did not show a statistically significant difference between the before and after measurements, however, in all these domains, the difference was such that the average score was less at the subsequent assessment. Total mean scores (composite scores) for the physical and psychological symptoms were analysed between the two time periods and the difference was statistically significant (z=3.828, p=0.0001). The difference between the before and after measurements for functional status was not statistically significant (z=-0.611, p=0.542). Conclusion: Patients with advanced cancer have a high symptom burden which affects their QoL. A PC approach appears to be effective in improving symptoms and QoL of patients with advanced cancer.